Can integrated infrastructure investment plans contribute to more effective public spending? The case of Mozambique - Mike Muller; Horacio Zandamela (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
All countries, especially developing countries with limited financial resources, face difficult decisions in prioritizing public funds for investment projects in order to achieve strategic public goals in the face of multiple demands. Effective investment often requires coordination between different institutions and the management of political pressure to divert investment in support of private interests. It also requires the identification of appropriate sources of funds for different purposes. The preparation of an integrated infrastructure investment plan (IIIP) that uses structured approaches to review investment proposals has been suggested, and adopted in some cases, as an instrument to address these challenges and bridge the gap between national planning and sectoral budgeting. This article considers the experience of Mozambique in deploying an IIIP and concludes that the instrument may be helpful as part of a system of investment planning and allocation but that it has significant limitations.
Keywords: O2; O20; H54; H61; O13; 330; infrastructure; development planning; budgeting; Mozambique